Analisis Label Halal pada Makanan Cepat Saji dalam Pengembangan Wisata Halal di Surabaya - Paramitha, Palupi; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2021)
The purpose of this study is to determine the understanding, assessment, and attitudes given by the community regarding the halal labeling of fast food sold by fast food business outlets and its impact on the development of halal tourism in Surabaya. This study uses a descriptive qualitative approach that aims to analyze public perceptions of the halal labeling of fast food. The object of research taken is located in Surabaya. This study uses two data sources which include primary data through online interviews and secondary data obtained from previous research literature. This study uses analysis technique that include data reduction, data presentation, and drawing conclusions. The results of this study indicate that the public has a high awareness of being more consumptive about the halal and haram of a product according to Islamic law and the MUI fatwa. The form of awareness in the form of supporting halal labeling obtained from MUI on the attributes of fast food business outlets in order to ensure the safety of the products consumed and minimize fraud committed by business actors. The positive impact of halal labeling is the development of halal tourism in the city of Surabaya, which provides an increase in the economy of local businesses and lures tourists to visit the city of Surabaya.